2015
DOI: 10.1111/jce.12848
|View full text |Cite
|
Sign up to set email alerts
|

Value of Cardiac Magnetic Resonance Imaging in Patients With Failed Ablation Procedures for Ventricular Tachycardia

Abstract: Imaging with DE-MRI prior to VT ablation in patients with previously failed endocardial ablation procedures is beneficial in identifying an ablation strategy, helps to focus on an area of interest intraprocedurally, and provides valuable outcomes information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Njeim et al reported a high proportion of septal late enhancement on MRI in 20 patients with unsuccessful ablation of VT 11. Haqqui et al reported that 11% of patients who underwent VT ablation had only a septal substrate 4.…”
Section: Discussionmentioning
confidence: 99%
“…Njeim et al reported a high proportion of septal late enhancement on MRI in 20 patients with unsuccessful ablation of VT 11. Haqqui et al reported that 11% of patients who underwent VT ablation had only a septal substrate 4.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent study demonstrated that preprocedural MRIs in patients with failed VT ablations also helped to localise the arrhythmogenic tissue and thereby indicated the likelihood of whether an epicardial ablation was necessary. 30 In this study, patients with cardiac implanted electronic devices (CIEDs) were included.…”
Section: Preprocedural Considerationsmentioning
confidence: 99%
“…[8][9][10][11][12] However, there have been no studies evaluating such techniques in refractory VAs exclusively in the NICM population. These studies have suggested improved outcomes with incorporation of epicardial access and ablation, or with the assistance of adjunctive tools, including advanced cardiac imaging and magnetic navigation technology.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have suggested improved outcomes with incorporation of epicardial access and ablation, or with the assistance of adjunctive tools, including advanced cardiac imaging and magnetic navigation technology. [8][9][10][11][12] However, there have been no studies evaluating such techniques in refractory VAs exclusively in the NICM population.…”
Section: Introductionmentioning
confidence: 99%